You are on page 1of 36

Heat Gain and Energy Balance of

Solar Collector

•Mohamad Kharseh

•E-mail:m.Kharseh@gmail.com

1
Useful Heat Gained By The Collector

Not all of solar radiation hits the sloped surface can be used:

Some solar radiation is reflected and re-emitted away

Some of the gained energy is lost again to the surrounding

qu = S⋅ Ap − ql

qu = Useful heat gained by the collector


S = Solar Energy absorbed in absorber
Ap = Area of the absorber plates
ql = Heat lost from the collector 2
Solar Energy absorbed in absorber

The absorbed solar radiation can be derived from the beam and diffuse
radiation incident on the collector.

S = (τα)b ⋅ GbT + (τα)d ⋅ (GdT + GrT )

(τα): Transmissivity-absorptivity product

The transmissivity-absorptivity product of diffuse radiation is


assumed to be the same as for beam radiation with incidence angle
60°
3
Solar Energy absorbed in absorber

 360 ⋅ n 
Gon = Gsc ⋅ 1 + 0.033 ⋅ cos 
 365 
τ b = ao + a1 ⋅ e( −k / cos θ z )

τ d = 0.271 − 0.294 ⋅ τ b

Gcd = τ d ⋅ Gon .(cosφ ⋅ cosδ ⋅ cosω + sinφ ⋅ sinδ )

Gcb = τ b ⋅ Gon .(cosφ ⋅ cosδ ⋅ cosω + sinφ ⋅ sinδ )


GbT = Gcb ⋅ Rb

 360 ⋅ n 
Gc = (τ b + τ d ) ⋅ Gsc ⋅ 1 + 0.033 ⋅ cos  ⋅ (cosφ ⋅ cosδ ⋅ cosω + sinφ ⋅ sinδ )
 365  GdT = Gcd ⋅ Rd
cos θ
Rb =
cos θ z
GrT = Gc ⋅ Rr
 1 + cos β 
Rd =  
 2 
 1 − cos β 
Rr =  
 2 
4
Transmissivity-absorptivity Product Of Beam

• The actual heat absorbed in the absorber is a result of:


1. The fraction of solar radiation that is transmitted through the cover
2. The fraction of this transmitted radiation that is absorbed in the
absorber

Diffuse reflectivity of
Transmissivity of the cover
the glass

1
S = (τα )b ⋅ IbT + (τα )d ⋅ ( )
Cover system
IdT + IrT
τ(1-α)ρd
τ
Absorptivity of
the absorber
τ(1-α) Absorber

5
τα τα(1-α)ρd τα(1-α)2 ρ2d
Transmissivity-absorptivity Product Of Beam

The radiation is reflected between the cover and absorber indefinitely


The sum of the absorbed fractions of the radiation is given as:

(τα ) = τ ⋅ α ⋅ [1 + (1 − α )ρd + (1 − α )2 ρd 2 + ...] = τ ⋅α


1 − (1 − α )ρd
(τα) Transmissivity -absorptivity product
τ Transmissivity of the glass
α Absorptivity of the absorber
ρd Diffuse reflectivity of the cover
1 cover: ρd = 0.15
2 covers: ρd = 0.22
6
Transmissivity Of The Beam

•The transmittance of the cover depends on the


incidence angle of the solar radiation.
The Transmissivity of the beam radiation must be
expressed as a function of: τa
1. transmittance due to reflection and refraction τr
2. transmittance due to absorption τ

τr, τa, τ
τ = τr ⋅ τa
7
Angle of incidence
Transmissivity due to Reflection and Refraction

•Transmissivity due to reflection and refraction


1 − ρ I 1 − ρ II
+
1 + ρ I 1 + ρ II
τr =
2
ρI, ρII Can be calculated use next equations:

sin 2 (θ r − θ ) tan 2 (θ r − θ )
ρI = ρ II =
sin 2 (θ r + θ ) tan 2 (θ r + θ )

The reflectance is a function of the angle of incidence and refraction


8
Transmissivity due to Reflection and Refraction

The relationship between the incidence θ and refraction θr angles is given by


Snell’s Law:

sinθ nglass
=
sinθ r nair θ

n1 and n2 are the refractive indices of air and


glass, respectively.

(nglass/nair = 1.526)
θr

9
Transmissivity due to Absorption

Transmissivity due to absorption


The transmittance for beam radiation is a function of the absorptivity
of the cover material (no reflection)

τa = e( )
−K ⋅δc
Bouger’s Law: cosθr

δc is the thickness of the cover (glass)

K is the extinction coefficient of the cover material.


Usually, 5 ≤ K ≤ 25 m-1
10
Transmissivity-absorptivity Of Diffuse

Transmissivity-absorptivity product of diffuse radiation


Since diffuse radiation comes from all directions, it is not possible
to derive an exact expression.

Transmissivity -absorptivity product for diffuse radiation (τα)d is


assumed to be equal to that for beam radiation at 60° incidence
angle

11
Solar Energy Absorbed in Absorber

for more accuracy

S = (τα )b ⋅ GbT + (τα )d ⋅ GdT + (τα )g ⋅ GrT

(τα)b: Transmissivity-absorptivity product of beam radiation

at incident angle θ

(τα)d: Transmissivity-absorptivity product of diffuse radiation

at incident angle θd

(τα)g: Transmissivity-absorptivity product of reflected radiation

at incident angle θg
12
Solar Energy Absorbed in Absorber

θd = 59.7 − 0.1388 ⋅ β + 0.001497 ⋅ β 2


θg = 90 − 0.5788 ⋅ β + 0.002693 ⋅ β 2 13
Liquid Flat Plate Collectors

1. Heat Loss from Collector

2. Testing of Solar Collectors

14
Useful Heat Gained By The Collector

Not all of solar radiation hits the sloped surface can be used:

Some solar radiation is reflected and re-emitted away

Some of the gained energy is lost again to the surrounding

qu = S⋅ Ap − ql

qu = Useful heat gained by the collector


S = Solar Energy absorbed in absorber
Ap = Area of the absorber plates
ql = Heat lost from the collector 15
Heat Losses from Collector
•The thermal losses depends on:
• The temperature difference between the absorber
plate and the ambient air
• The overall heat loss coefficient, Ul [W/m2,K]

(
q l = U l ⋅ A p ⋅ Tpm − Ta )
Tpm = Mean temperature of absorber plates
Ta = Ambient air temperature

16
Heat Losses from Collector
•Whenever the absorber plate is warmer than the
ambient air, heat is lost from the collector through:
(
qt = Ut ⋅ Ap ⋅ Tpm − Ta )
• the cover (top), [W]
qb = U b ⋅ Ap ⋅ (Tpm − Ta )
• the bottom, [W]
(
qs = Us ⋅ Ap ⋅ Tpm − Ta )
• the sides, [W]

Most of the heat losses is through the cover

17
Overall Heat Loss Coefficient
Then, the total heat losses is:

q l = qt + q b + qs

•Since the heat loss equations are expressed on the basis of


the same temperature difference, it is then possible to
evaluate the overall heat loss coefficient, Ul, by

ql = U l ⋅ Ap ⋅ (Tpm − Ta )

U l = Ut + U b + Us

Typical values of Ul ranges from 2 to 10 W/m2K


18
Thermal Network for a Flat-Plate

qu

19
Bottom Heat Losses Coefficient
•The heat losses coefficient through the bottom is
represented by two series resistors, R3 and R4. It is
possible to assume R4 is zero:

1 λ
Ub = =
R3 δ b

λ = thermal conductivity of insulator


δb = thickness of insulated bottom

20
Side Loss Coefficient
Similarly, the heat transfer coefficient for the collector side is:

2 ⋅ L3 ⋅ (L1 + L2 ) λ
Us = ⋅
L1 ⋅ L2 δs

L1= length of casing


L2= width of casing
L3= height of casing
λ= thermal conductivity of insulation
δs = thickness of insulated side
21
Top Loss Coefficient
−1
   


Ut = 
N 1
+ 
 
+
σ ⋅ T (
2
pm + Ta
2
⋅ T)(
pm + T )
a


 Tpm − Ta 
e αa   1 2N + f − 1 + 0.133 ⋅ ε p 
 C  + −N
T ⋅    ε + ⋅ ⋅ α ε
 N +f   p 0.00591 N a g 
 pm 

α a = 5.7 + 3.8 ⋅ v wind or α a = 2.8 + 3 ⋅ v wind or Nu = 0.86 Re1/ 2 Pr1/ 3

( )
f = 1 + 0.089 ⋅ α a − 0.1166 ⋅ α a ⋅ ε p ⋅ (1 + 0.07866N )

N = number of covers
C = 520 ⋅ ( 1 − 0.000051 ⋅ β ); 0 ≤ β ≤ 70
2
σ = Stefan-Boltzmann constant
εp = emissivity of plate
100
e = 0.43 ⋅ ( 1 − ) εg = emissivity of glass (0.88)
Tpm
αa = convection coefficient of ambient air (W/m2K)
νwind =Wind speed of ambient air (m/sec)
22
β = collector tilt (degree)
Heat Balance of Collector

( (
qu = Ap S − U l Tpm − Ta ))

•This expression depends on two factors:


1. Ul : is a function of the mean plate temperature, Tpm
2. Tpm: is the mean plate temperature, which is unknown

•We need to express qu in terms of a known temperature.


• The only known temperature is the fluid inlet temperature

23
Absorber Cross-section
•The useful heat gained by the absorber plate can be divided into:
1.the heat gained from the area above the tube
2.the heat gained from the fin

qu′ = qu′ tube + qu′ fin

tube fin

W-Do
W 24
Heat Gain per unit Length
The useful heat transfer rate to the fluid in the absorber cross-section is:

qu′ = [F ⋅ (W − Do ) + Do ] ⋅ [S − U l (Tb − Ta )]

F: Standard Fin Efficiency

tanh[m ⋅ (W − Do )/ 2]
F=
m ⋅ (W − Do )/ 2

Hyperbolic
tangent
Do= tube outer diameter
W = distance between tubes
Where m is :
Tb = local absorber temperature above the bond
m = (Ul/λpδp)½
λp = thermal conductivity of absorber plate
δp = thickness of absorber plate 25
Collector Efficiency Factor, F′
qu′ = [F ⋅ (W − Do ) + Do ] ⋅ [S − U l (Tb − Ta )]

To relate this expression to the local fluid temperature that results from
this heat transfer, the collector efficiency factor, F’, is introduced:

U0 1
F' = =
Ul  1 1 
WU l  + 
U l ⋅ [F (W − Do ) + Do ] πDi α f 

Di= tube inner diameter


αf = convection coefficient of fluid
Uo= overall heat loss coefficient from fluid to ambient
Ul = overall heat loss coefficient from absorber to ambient
26
Collector Efficiency Factor, F′
Thus, useful gain can be expressed as :

qu′ = F ′ ⋅ W ⋅ [S − U l (Tf − Ta )]

We eliminated Tb from the equation and obtain an


expression for useful gain in term of known dimensions,
physical parameters and fluid temperature.

27
Heat Gain in Cross-section

We can express an energy balance on the fluid flowing


through a signal tube of a small length dy as:

Fluid Flow  /n) ⋅ c pTf (y)


(m  /n) ⋅ c pTf (y + dy)
(m

dy
y
Number of tube in
the absorber plate

n ⋅ qu′ ⋅ dy = m  ⋅ c p ⋅ dTf − n ⋅ F' ⋅ W ⋅ [S − U l (Tf − Ta )] = 0


 ⋅ c p ⋅ dTf ⇒ m
dy
28
Heat Gain in Cross-section
•Solving this differential equation, we can determine the fluid
temperature at any position y:

 Ul ⋅n ⋅W ⋅F ' 
- y

Tf (y)-Ta -S/U l  m ⋅c p 
=e 
Tfi -Ta -S/U l

If the collector has a length L in the flow direction, then the


outlet fluid temperature Tfo is found by substituting L for y, note
that “n.W.L =Ap”

 Ul ⋅ Ap⋅F' 
- 
Tfo -Ta -S/U l  m  ⋅c p 
= e 
Tfi -Ta -S/U l 29
Heat Removal Factor, FR
•The heat removal factor, which relates the actual heat gain to the
maximum heat gain, is define as:

qu Actual hea t gain  ⋅ c p (Tfo − Tfi )


m
FR = =
qu Maximum heat gain Ap [S − U l (Tfi − Ta )]

Using the last equation in the previous slide, we can express


FR that is independent of the outlet temperature, Tfo:

 

Ul ⋅ Ap  


mc p  
− F' ⋅
m ⋅Cp 
FR = 1 − e  
U l Ap  
 
 
30
Heat Gain in Cross-section

Then the collector heat removal factor times this


maximum possible useful energy gain is equal to
the actual useful energy gain qu

qu = Ap ⋅ FR [S − U l (Tfi − Ta )]

31
Heat Gain in Cross-section
•Using FR the useful heat gain can now be determined
based on the inlet temperature.
• But the overall heat loss coefficient, Ul, is a function of the
mean plate temperature, Tpm
  − F' ⋅ l p  
 U ⋅A 

mc p   m ⋅Cp   qu = Ap ⋅ FR [S − U l (Tfi − Ta )]
FR = 1 − e  
U l Ap  
 
 

U0 1
F' = =
Ul  1 1 
WU l  + 
U l ⋅ [F (W − Do ) + Do ] πDi α f 

U l = Ut + U b + Us

−1
   


Ut = 
N
+
1

+

(
σ ⋅ Tpm
2
)(
+ Ta2 ⋅ Tpm + Ta ) 

  + − + ⋅ ε 
 C  Tpm − Ta 
e αa  1 2 N f 1 0.133 p
⋅    + −N
T +   ε p + 0.00591⋅ N ⋅ α a εg  32
 pm  N f  
Mean Plate Temperature
1. Guess a first value of Ul (2 – 10 W/m2,K) and calculate
the heat gain, qu.
2. Tpm can then be calculated from the original heat gain
equation:
( (
qu = Ap S − U l Tpm − Ta ))

3. Use the calculated Tpm to derive a new Ul.


4. Continue with iterations until Ul remains approximately
the same from one calculation to another.
• Since Ul is only vaguely dependent on the temperature,
one or two repetition should be necessary
33
Instantaneous Collector Efficiency
•Collector is exposed to solar radiation while the fluid flow
rate and temperature increase is measured.

• The useful heat gain in a collector operating under steady


state condition equals the enthalpy increase of the fluid:
(
qu=m c p T fo -T fi )
• The instantaneous collector efficiency is the ratio of the useful
heat gain to the incident solar radiation:

ηi=
qu
=
( )
m c p T fo -T fi FR
= [S-U (T -T )]
L fi a
Ap I T Ap I T IT 34
Instantaneous Collector Efficiency
•The efficiency curve for a collector is plotted as a function of (T fi – Ta)/IT

[Tfi-Ta/IT]⋅103 [K⋅m2/W]

The efficiency curve yields a straight line since FR, (τα) and Ul are
fairly constant for a collector type when the flow rate is constant
35
S = (τα)b ⋅ GbT + (τα)d ⋅ (GdT + GrT )

τ ⋅α
(τα ) =
1 − (1 − α )ρd

qu = Ap ⋅ FR [S − U l (Tfi − Ta )]

  − F' ⋅ l p  
 U ⋅A 
U0 1

mc p   m ⋅Cp   F' = =
FR = 1 − e   Ul  1 1 
U l Ap   WU l  + 



 U l ⋅ [F (W − Do ) + Do ] πDi α f 

U l = Ut + U b + Us

−1
   


Ut = 
N
+
1

+

( 2 2
)(
σ ⋅ Tpm + Ta ⋅ Tpm + Ta ) 

  2N + f − 1 + 0.133 ⋅ ε p 
 C  Tpm − Ta 
e αa  1
⋅   + −N
T    ε p + 0.00591⋅ N ⋅ α a εg  36
 pm  N +f  